2013
DOI: 10.1523/jneurosci.4278-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Corticotropin-Releasing Factor and Neuropeptide Y within the Dorsolateral Bed Nucleus of the Stria Terminalis in the Negative Affective Component of Pain in Rats

Abstract: Pain is a complex experience composed of sensory and affective components. Although the neural systems of the sensory component of pain have been studied extensively, those of its affective component remain to be determined. In the present study, we examined the effects of corticotropin-releasing factor (CRF) and neuropeptide Y (NPY) injected into the dorsolateral bed nucleus of the stria terminalis (dlBNST) on pain-induced aversion and nociceptive behaviors in rats to examine the roles of these peptides in af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 43 publications
3
66
0
Order By: Relevance
“…This test, in which mice learn to avoid a chamber where they experienced pain induced by formalin injection to the hind paw, has been used extensively to investigate the affective component of pain in rodents (3,5,6,8). To explore the role of prostaglandins, we first interfered with the cyclooxygenases COX1 and COX2 (also known as PTGS1 and PTGS2), enzymes responsible for prostaglandin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…This test, in which mice learn to avoid a chamber where they experienced pain induced by formalin injection to the hind paw, has been used extensively to investigate the affective component of pain in rodents (3,5,6,8). To explore the role of prostaglandins, we first interfered with the cyclooxygenases COX1 and COX2 (also known as PTGS1 and PTGS2), enzymes responsible for prostaglandin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas PKC-δ + neurons in the CeA L represent -fear off‖ neurons (Haubensak et al, 2010), perhaps Type II PKC-δ + cells represent -anxiety off‖ neurons in the BNST ( Figure 1D). In addition to inhibition via local GABAergic connections, CRF action and CRF neurons themselves are opposed by NPY (Ide et al, 2013;Kash and Winder, 2006;Pleil et al, 2015). In fact, NPY in the BNST has been shown to block CRF-induced-place aversion (Ide et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inhibition via local GABAergic connections, CRF action and CRF neurons themselves are opposed by NPY (Ide et al, 2013;Kash and Winder, 2006;Pleil et al, 2015). In fact, NPY in the BNST has been shown to block CRF-induced-place aversion (Ide et al, 2013). More studies on peptides and the local circuitry involved in the regulation of CRF neuron activity are needed to better understand how the BNST modulates anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…receptor antagonists, BIBP-3226 and L-152,804, respectively (Ide et al, 2013). Although many studies have found that NPY typically reduces synaptic transmission, it is interesting to note that NPY can also enhance inhibitory transmission.…”
mentioning
confidence: 99%